Optical coherence tomography findings of macula and neural changes in cryptococcal meningitis - Simin Gu; Yaqi Cheng; Huini Zhang; Jiayi Lin; Tao Wang; Shiqi Ling (Photodiagnosis and Photodynamic Therapy)
Purpose: To investigate the structures and neural changes in cryptococcal meningitis (CM) patients compared with healthy controls. Design: Retrospective, cross-sectional, cohort study. Methods: Seventy-six eyes of 39 CM patients were included in this observational clinical cohort study. Thirty eyes of 16 CM patients with papilledema were included in Group 1, and 46 eyes of 23 CM patients without papilledema were included in Group 2. Another 80 eyes of 40 healthy participants were included in Group 3 as controls. Optical coherence tomography (OCT) images were obtained from all the participants via a DRI OCT Triton 3D device with its prototype IMAGEnet 6 for OCT software. Results: Compared with those of the controls, the peripapillary retinal nerve fiber layer thickness (pRNFLT), peripapillary GCL++ thickness [pGCL++T, including the RNFL, ganglion cell layer (GCL), and inner plexiform layer (IPL)], peripapillary GCL+ thickness (pGCL+T, including the RNFL and IPL) and peripapillary choroidal thickness (pCT) were dramatically increased in CM patients with papilledema but decreased in those from CM patients with no papilledema. There was a similar trend in macular GCL++ thickness (mGCL++T) and macular GCL+ thickness (mGCL+T) in CM absent from optic swelling when compared with healthy controls. Conclusion: Papilledema may or may not be present depending on the timing of the evaluation, and the ophthalmologic manifestations of CM with papilledema can be well observed. However, changes in the optic nerve head (ONH) and peripapillary structures in CM patients with no papilledema can be detected by optical coherence tomography. Parameters such as pRNFLT, pGCL++T, pGCL+T and pCT may provide useful evidence for the early detection of structures and neural impairments in patients with CM.